Analisa Kinerja Pegawai Pada Dinas Pemberdayaan Masyarakat dan Desa Kabupaten Bekasi - Hikmah Fauziah; Dadan Kurniansyah; Made Panji Teguh Santoso (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to examine and analyze as well as determine the analysis of employee performance at the Bekasi Regency Community and Village Empowerment Service (DPMD). This research is a descriptive qualitative type with data collection techniques carried out using triangulation which includes interviews, observations and documentation studies, then the data is analyzed by reducing, presenting and drawing conclusions. The theory used is the performance of Suyadi Prawirosentono (2008:27) with four dimensions, namely effectiveness, responsibility, initiative and discipline. The results of this study indicate that the performance of DPMD Bekasi Regency employees can be said to be good for all dimensions, so that the performance of DPMD employees can run quite optimally according to the needs and desires of the community and other bureaucracies related to the Bekasi Regency DPMD.